2004
DOI: 10.1124/jpet.104.075770
|View full text |Cite
|
Sign up to set email alerts
|

Blood Clearance and Activity of Erythrocyte-Coupled Fibrinolytics

Abstract: Conjugating tissue-type plasminogen activator (tPA) to red blood cells (RBCs) endows it with features useful for thromboprophylaxis. However, the optimal intensity and duration of thromboprophylaxis vary among clinical settings. To assess how the intrinsic properties of a plasminogen activator (PA) affect functions of the corresponding RBC/PA conjugate, we coupled equal amounts of tPA or Retavase (rPA; a variant with an extended circulation time, lower fibrin affinity, and greater susceptibility to PA inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
90
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 34 publications
2
90
0
Order By: Relevance
“…Results of previous studies have shown that coupling tPA to RBCs increased its intravascular life span compared with soluble tPA. 51 One possible explanation for this surprising result is that coupling to RBCs renders tPA less susceptible to plasma tPA inhibitors, 52 including the most physiologically relevant plasminogen activator inhibitor 1 (PAI-1). Further studies affirm the greater fibrinolytic potency of bound tPA compared with soluble tPA in mouse blood, and indicate that coupling to RBCs protects tPA against physiological and pathological concentrations of PAI-1, 53 and inhibition by other serpins (α 2 -macroglobulin and α 1 -antitrypsin).…”
Section: Activity Retention (%)mentioning
confidence: 99%
“…Results of previous studies have shown that coupling tPA to RBCs increased its intravascular life span compared with soluble tPA. 51 One possible explanation for this surprising result is that coupling to RBCs renders tPA less susceptible to plasma tPA inhibitors, 52 including the most physiologically relevant plasminogen activator inhibitor 1 (PAI-1). Further studies affirm the greater fibrinolytic potency of bound tPA compared with soluble tPA in mouse blood, and indicate that coupling to RBCs protects tPA against physiological and pathological concentrations of PAI-1, 53 and inhibition by other serpins (α 2 -macroglobulin and α 1 -antitrypsin).…”
Section: Activity Retention (%)mentioning
confidence: 99%
“…Previous in vivo studies show that RBC carriage overrides differences in pharmacokinetics among soluble PAs (Ganguly et al, 2005). Thus, soluble tPA is cleared from the blood more rapidly than rPA (Retavase), a truncated tPA variant lacking the growth factor (G), finger (F), and first kringle (K1) domains (Kohnert et al, 1992).…”
mentioning
confidence: 99%
“…Thus, soluble tPA is cleared from the blood more rapidly than rPA (Retavase), a truncated tPA variant lacking the growth factor (G), finger (F), and first kringle (K1) domains (Kohnert et al, 1992). Yet, both RBC/tPA and RBC/rPA circulate for at least many hours in animals (Murciano et al, 2003;Ganguly et al, 2005). Previous studies also revealed that coupling to RBCs attenuates tPA inhibition by PAI-1 (Ganguly et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reteplase (Retavase, PDL BioPharma) is a nonglycosylated recombinant plasminogen activator variant derived from human tissue-type plasminogen activator and having a 4-fold longer half-life than tPA, permitting bolus injection. 14,15 It is cleared from the plasma in a biphasic manner, with a half-life of about 1 minute in the ␣-phase (28% cleared) and 20 to 28 minutes in the ␤-phase (72% cleared). 16 The findings of the present study show that the addition of albumin to subthrombolytic doses of reteplase results in a robust improvement of microvascular hemodynamics distal to an arteriolar thrombosis.…”
mentioning
confidence: 99%